Service Print Advertisements: Analyzing the Impact of Emotions and Attitudes on Consumption Intentions - Sciulli, Lisa M; Bebko, Charlene (Journal of Research in Marketing (ISSN: 2292-9355), 2019)
A model is proposed whereby the influence of emotional appeals and attitude toward the ad on service consumption intentions are examined. Regression analysis revealed both emotion and attitudes significantly influence consumers’ future behaviors for all ten service types studied with exception of emotions for delivery services. The research findings further indicate that while both influence consumption, attitude toward the ad had a stronger influence than emotions across all ads tested. It can be inferred that happiness had the strongest influence on emotion followed by good, and then usefulness and high quality were the strongest attitudinal indicators impacting intentions. Conclusions will discuss the importance and applicability of emotions and attitudes for advertising planning and managerial implications.